The reality of administrative leadership practices, human resources, partnerships and resources among the employees of the Tawafa Establishment for Pilgrims of Non- Arab African Countries: Evaluation study - Zahrani, Mahboobh Ahmad Braidy (Journal of Economic, Administrative and Legal Sciences, 2021)
This study seeks to identify the reality of the practices of administrative leadership, human resources, partnerships and resources (financial resources management, technology and knowledge management) among employees of the Tawafa Establishment for pilgrims of non- Arab African countries. (Evaluation study) according to the Excellence Model of King Abdulaziz Quality Award, the unified national model for quality and institutional excellence for all sectors in the Kingdom of Saudi Arabia. Which will contribute to achieving institutional excellence for the raft institutions and achieving competitiveness? The researcher used the descriptive analytical approach as a methodology to achieve the goal and purpose of the study, and to obtain the results of the study, the researcher designed the study tool represented in the questionnaire. In order to collect primary information from the study sample. In light of this, data were collected, analyzed and hypotheses tested using the SPSS statistical package, the sample of the study consisted of (42) employees working in the Tawafa Establishment for pilgrims of non- Arab African countries. The main problem and dilemma of the study is to stand at the administrative level at all levels in all technical and human aspects, according to the standards of administrative leadership and the extent to which they are related to human values ​​and behaviors, through strenuous efforts in implementing and applying everything that is possible to apply And in line with the possibilities of the Excellence Model of the King Abdul Aziz Award for Quality, the unified national model for quality and institutional excellence for all sectors in the Kingdom of Saudi Arabia, and this study aims to create a clear picture of scrutiny and audit of the administrative levels in the institution to achieve the desired goal of that study, which includes strengthening relations With groups of concerned parties to ensure the achievement of the strategic direction and the establishment of systems to support a culture of quality, excellence and creativity, in addition to seeking to implement the principles and requirements of social responsibility, corporate governance and transparency in order to achieve sustainable development, as strategic leadership practices are considered important and necessary for its success through attention to human resources by providing a work environment; attractive to them and for their health, safety and well- being in order to achieve Institutional loyalty. The importance of this study is theoretically due to the attempt to enrich the study concepts and literature on the application of some possibilities of the Excellence Model of the King Abdulaziz Quality Award, the unified national model for quality and institutional excellence for all sectors in the Kingdom of Saudi Arabia. The study is also concerned with the possibility of a reference to be prepared for all researchers and those interested in the field of institutional transformation strategies, resistance to change, and improving the performance of workers, in the raft institutions. From an applied point of view, the importance of the study lies in the possibility of applying the results and recommendations in the institution of pilgrim’s employees of non- Arab African countries in the Kingdom of Saudi Arabia, and addressing weaknesses and shortcomings. The researcher used the descriptive analytical approach, which depends on the methods of measurement, classification and interpretation in order to extract significant conclusions in addition to documents and other sources such as books, magazines, and others. The study included several results in line with the main axes on which the questionnaires depended. Pilgrims of non- Arab African countries to a very large extent, the strategic direction according to the excellence model of the King Abdul Aziz Prize for Quality, the unified national model for quality and institutional excellence, as well as in the review of the administrative system and institutional performance. Perhaps one of the most important results of the study is managing change, managing risks and crises according to the excellence model of the King Abdul Aziz Quality Award, the unified national model for quality and institutional excellence with a high degree of domesticity within the institution. While the results of the second and third axes included results of medium degrees in terms of developing the knowledge and capabilities of human resources according to the Excellence Model of the King Abdul Aziz Prize for Quality, the unified national model for quality and institutional excellence, as well as financial management.